2001
DOI: 10.1006/gcen.2000.7553
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Characterization, and Tissue Distribution of Prolactin Receptor in the Sea Bream (Sparus aurata)

Abstract: The prolactin receptor (PRLR) was cloned and its tissue distribution characterized in adults of the protandrous hermaphrodite marine teleost, the sea bream (Sparus aurata). An homologous cDNA probe for sea bream PRLR (sbPRLR) was obtained by RT-PCR using gill mRNA. This probe was used to screen intestine and kidney cDNA libraries from which two overlapping clones (1100 and 2425 bp, respectively) were obtained. These clones had 100% sequence identity in the overlapping region (893 bp) and were used to deduce th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 61 publications
6
57
0
Order By: Relevance
“…The function of the saccus has been suggested to be mainly concerned with homeostasis of the cerebrospinal fluid; others have suggested that it may be concerned with osmoregulation via the activity of ATPase enzymes involved in transport of Na + /K + and Mg 2+ /Ca 2+ (Jansen et al 1981). Observations of the presence of immunoreactive IGF-II (present study) and IGF-I (G Radaelli, M Patruno, L Maccatrozzo & B Funkenstein, unpublished observations) in the saccus of S. aurata, together with previous reports on immunoreactive prolactin receptors in this organ of S. aurata (Santos et al 2001) further support a role in osmoregulation. Other organs involved in osmoregulation also exhibited IGF-II immunoreactivity in the current study: skin, epithelial cells of the gill filaments and epithelium of kidney tubules.…”
Section: Discussionsupporting
confidence: 86%
“…The function of the saccus has been suggested to be mainly concerned with homeostasis of the cerebrospinal fluid; others have suggested that it may be concerned with osmoregulation via the activity of ATPase enzymes involved in transport of Na + /K + and Mg 2+ /Ca 2+ (Jansen et al 1981). Observations of the presence of immunoreactive IGF-II (present study) and IGF-I (G Radaelli, M Patruno, L Maccatrozzo & B Funkenstein, unpublished observations) in the saccus of S. aurata, together with previous reports on immunoreactive prolactin receptors in this organ of S. aurata (Santos et al 2001) further support a role in osmoregulation. Other organs involved in osmoregulation also exhibited IGF-II immunoreactivity in the current study: skin, epithelial cells of the gill filaments and epithelium of kidney tubules.…”
Section: Discussionsupporting
confidence: 86%
“…Since such high extrapituitary expression has been reported only in teleosts such as rainbow trout, goldfish and other perciforms (Santos et al 1999, Yang et al 1999, Imaoka et al 2000, production of PRL might be centralized into pituitary during terrestrial tetrapod evolution. The larger size of extrapituitary PRL transcripts may reflect a difference of promoter usage as reported in mammalian lymphocytes and decidua, whose RNA transcripts are larger than the pituitary counterpart (Ben-Jonathan et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the control of extrapituitary PRL expression is still poorly understood, both at the transcriptional and at the secretory levels (Goffin et al 2002). Since extrapituitary PRL expression in trout, goldfish and seabream has been reported to be relatively high, unlike that in tetrapods (Santos et al 1999, Yang et al 1999, Imaoka et al 2000, studies using aquatic teleosts should shed new light on the regulation of extrapituitary PRL in terrestrial vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…PRLR sequences have been characterised for several species of fish, including goldfish [113], seabream [95], blue discus (Symphysodon aequifasciatus) [52], Japanese flounder (Paralichthys olivaceus) [41], starry flounder [72], fugu [59], and Nile tilapia [92]. These genes encode mature peptides of ca.…”
Section: Prolactin Receptormentioning
confidence: 99%
“…Firstly, PRLR mRNA and mature protein have been found in the gonads of a number of fish species, including Mozambique tilapia [31], Nile tilapia [91], seabream [20,95], Japanese flounder [41], goldfish [113], fugu (Takifugu rubripes) [59], and starry flounder [72], suggesting that PRL may be involved in spermatogenesis, vitellogenesis, and/or ovulation. Further studies involving immunohistochemical analyses of fish gonads across the full reproductive cycle are required to clarify these functions.…”
Section: Reproductive Development and Cyclingmentioning
confidence: 99%